Kinerja Keuangan Pada PT. Bakrieland Development TBK - Rosmiaty Tarmizi; . Selviana; Ardansyah ARDANSYAH (Universitas Bandar Lampung (UBL), 2013)
This study aims to search how liquidity and profitability of PT. Bakrieland Development Tbk in period 2007-2011. In another hand, this research also describe related to this performance. The reserach found that in periode 2007-2011, financial performance PT. Bakrieland Development Tbk has unstable condition. Thi condition reflected from Â liquidity ratio (current ratio) and also profitability (ROI).